Pengaruh Konstitusi Berketuhanan Dalam Praktik Ketatanegaraan (Perbandingan Antara Indonesia Dengan Berbagai Negara) - Sujatnika, Ghunarsa (UI Scholars Hub, 2018)
One debate that has been going on for a long time and has not yet been completed is related to the relationship between religion and the state. There are two general opinions on this matter, namely that which separates religion and state life and vice versa argues that religion is an integral part of the life of the state. One way to see how the relationship between God and religion and the state can be seen in the country's constitution, whether the constitution regulates